Estudo da interação genótipo-ambiente em rebanhos da raça Nelore na Amazônia Legal - MATOS, Amanda de Sousa (Universidade Federal do Pará, 2014)
Data from adjusted weights at 120 (P120), 210 (P210), 450 (P450) days of age, scrotal circumference at 450 days of age (PE450) and age at first calving (IPP), for 211,744 records from Nelore herds located in the Legal Amazon region, were used in the analysis. The effect of genotype-environment interaction was studied through heritability estimates and correlations between ranks, comparing the Legal Amazon animals with the general basis of animals – PMGRN Nelore Brazil. Bi-trait analyses considered P120 as anchor-trait, with P210, P450 and PE450 as another one. Model considered contemporary group of P120, P210, P450 and age-of-dam classes as fixed effects and direct maternal, additive and residual as random effects. Analyses of P120 with P450 and PE450 not included maternal effect in the model. Covariance additive-maternal was fixed at zero, as protocol in PMGRN – Nelore Brazil analysis. IPP has been analyzed separately in single-trait analysis and considering GCIPP as fixed and additive and residual effects as random. Comparisons between ranks, through the procedure PROC CORR option spearman of SAS were obtained. Estimates of heritability for P120, P210, P450, PE450 and IPP on the data of the Legal Amazon were: 0.20 to 0.49; 0.21; 0.48; 0.45; and 0.21, respectively, and in general data of PMGRN – Nelore Brazil were: 0.23; 0.25; 0.34; 0.43 and 0.11, respectively. Correlations between rank for P120, P210, P450, PE450 and IPP were equal to 0.77; 0.79; 0.82; 0.78 and 0.38, respectively. The analysis of genotype-environment interaction have demonstrated greater effects on maternal, IPP and P450, while correlations between classifications showed strong evidence in almost all traits studied.